SELF-MEDICATION ANTIBIOTIK DI MASYARAKAT INDONESIA: TINJAUAN LITERATUR MENGENAI HUBUNGAN DENGAN TINGKAT PENDIDIKAN DAN IMPLIKASI UNTUK INTERVENSI PENDIDIKAN KESEHATAN - Maryeti Marwazi; Elfi Yulfienti (Yayasan Nusantara Hasana Berdikari, 2025)
Antibiotic self-medication (ASM) is a significant public health concern that contributes to antimicrobial resistance (AMR). The role of educational attainment in shaping community practices related to ASM remains inconsistent across studies. To review empirical evidence on the prevalence of ASM in Southeast Asia and Indonesia, to analyze the association between educational level and ASM practices, and to formulate evidence-based educational intervention recommendations. A narrative literature review with a systematic approach was conducted by identifying secondary studies (systematic reviews and meta-analyses) and empirical national/regional studies published in English or Indonesian between 2010 and 2025. Searches were performed in accessible databases and institutional repositories. The review focused on ASM prevalence, associated determinants (including educational level), and educational intervention strategies. Detailed search strategies and inclusion criteria are described in the Methods section. Systematic evidence indicates that ASM remains highly prevalent in Southeast Asia. In Indonesia, widespread access to antibiotics without prescription persists, alongside variability in the association between educational level and ASM practices. Several studies and meta-analyses report that higher educational attainment is associated with reduced odds of antibiotic misuse in certain contexts; however, this association is not consistent across regions. Other determinants—including access to medications, storage of leftover antibiotics, the role of pharmacies, socioeconomic status, and health literacy also play substantial roles. Educational level influences antibiotic use practices; however, interventions that target formal education alone may be insufficient. Contextualized health education interventions integrating regulatory enforcement on antibiotic distribution, pharmacist training, and community-based awareness campaigns—are more likely to effectively reduce ASM and mitigate AMR progression.